Platycrus—a remarkable new genus of the tribe Platynaspini (Coleoptera: Coccinellidae) from Laos - Szawaryn, Karol; Ślipiński, Adam (Zootaxa, 2022)
A new remarkable ladybird beetle Platycrus laotanus gen. et sp. nov. is described from Laos. It is placed in the tribe Platynaspini, but it differs from the remaining members of the tribe by having unusually expanded legs, a peculiar pocket-like structure to accommodate the tarsi in repose, and the antennae consisting of 11 antennomeres. Detailed morphological description and illustrations are provided. Taxonomic placement of the newly described taxon is discussed, and a transfer of the genera Crypticolus Strohecker and Hornious Weise from Platynaspini to Coccinellinae as incerte sedis.